2022
DOI: 10.3928/24748307-20220616-01
|View full text |Cite
|
Sign up to set email alerts
|

A Descriptive Analysis of Cancer Screening Health Literacy Among Black Women Living with HIV in Baltimore, Maryland

Abstract: Background: Black women living with HIV (WLH) have the highest HIV infection rate, cervical cancer mortality, and the lowest cancer screening use compared to other groups. However, there is a gap in knowledge about cancer screening health literacy in the Black WLH population. Objective: The purpose of this study was to assess the level of cancer screening health literacy, and to identify factors associated with health literacy among Black WLH. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…For example, in a recent cross-sectional study, nearly half (49.6%) of the Black WLH had a reading level at or below sixth grade, suggesting that the women may struggle with most written health information. 15 Systematic reviews and meta-analyses 16,17 of interventions designed to increase Pap screening participation among ethnic minority populations revealed that interventions have focused primarily on increasing knowledge (e.g., causes, risk factors or signs and symptoms of the disease) or accommodating women's needs and have produced small effect sizes of 5%-24%. None of the studies in these reviews has attempted to directly address study participants' health literacy deficits as a strategy to improve cancer screening participation rates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a recent cross-sectional study, nearly half (49.6%) of the Black WLH had a reading level at or below sixth grade, suggesting that the women may struggle with most written health information. 15 Systematic reviews and meta-analyses 16,17 of interventions designed to increase Pap screening participation among ethnic minority populations revealed that interventions have focused primarily on increasing knowledge (e.g., causes, risk factors or signs and symptoms of the disease) or accommodating women's needs and have produced small effect sizes of 5%-24%. None of the studies in these reviews has attempted to directly address study participants' health literacy deficits as a strategy to improve cancer screening participation rates.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of low health literacy is even higher among Black WLH. For example, in a recent cross‐sectional study, nearly half (49.6%) of the Black WLH had a reading level at or below sixth grade, suggesting that the women may struggle with most written health information 15 …”
Section: Introductionmentioning
confidence: 99%